(untitled) (CIPEEX, 2025)
Objective: The study aims to establish normative values for handgrip strength in the right and left hands of Brazilian adults of both sexes aged between 18 and 24 years. Material and Methods: A total of 41,591 subjects were evaluated, with a frequency of 23,931 women and 17,660 men, with an average age of 21.33 ± 1.99 years, a body mass of 69.38 ± 15.97 kg, and a height of 168.5 ± 9.2 cm, respectively; they were subjected to the manual pressure strength test using the hydraulic dynamometer "Force" provided by Tera Science, through secondary data provided by the aforementioned company. Results: The results show that women had a strength of 24.24 ± 5.44 kgf in the left hand and 25.99 ± 5.56 kgf in the right hand, while men obtained 39.68 ± 8.96 kgf in the left hand and 41.95 ± 9.29 kgf in the right hand. Conclusion: This study provides an initial contribution to the normative values of handgrip strength in the Brazilian population aged between 18 and 24 years.